The impact of hearing disorders on the body balance - Ewelina Stefania Pankanin (Kazimierz Wielki University, 2018)
Body balance is one of the basic human motor skills. The efficient functioning of the balance system depends on the proper functioning of the balance organ, the deep sense and vision organ. Any dysfunctions in operation, any of the above systems interfere with the balance system. Hearing pathologies seem to be closely related to the maintenance of balance, due to the integrity in the construction of the organ of balance and the organ of hearing and the huge role that hearing plays in the orientation in space.